2005
DOI: 10.1088/1009-9271/5/s1/353
|View full text |Cite
|
Sign up to set email alerts
|

Astrophysical Quark Matter

Abstract: The quark matter may have great implications in astrophysical studies, which could appear in the early Universe, in compact stars, and/or as cosmic rays. After a general review of astrophysical quark matter, the density-dominated quark matter is focused.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The idea of SQM originated some time ago in Terazawa (1979); Witten (1984); Farhi & Jaffe (1984); Alcock & Farhi (1985), but it remains alive, cf. Madsen (1999); Alford (2009); Weber (2005); Xu (2005); Klingenberg (2001); Terazawa (2015Terazawa ( , 2016 1 . In short, the basic, commonly accepted view is that that SQM (understood as a combination of roughly an equal number of up, down and strange quarks) might be the true ground state of quantum chromodynamics (QCD).…”
Section: Introductionmentioning
confidence: 99%
“…The idea of SQM originated some time ago in Terazawa (1979); Witten (1984); Farhi & Jaffe (1984); Alcock & Farhi (1985), but it remains alive, cf. Madsen (1999); Alford (2009); Weber (2005); Xu (2005); Klingenberg (2001); Terazawa (2015Terazawa ( , 2016 1 . In short, the basic, commonly accepted view is that that SQM (understood as a combination of roughly an equal number of up, down and strange quarks) might be the true ground state of quantum chromodynamics (QCD).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important phase transitions of the universe is the Quark Gluan Plasma (QGP)→ hadron gas transition (called quark-hadron phase transition) when the cosmic temperature was T ∼ 200 MeV (Xu 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8]). For the shallow decay phase, Nousek et al [1] and Zhang et al [3] supposed that they come from late energy re-injection; Toma et al [4] proposed a special jet profile; Zou and Dai [7] and Xu and Huang [9] thought that they may be tail emissions from a slow ring-like jet; Fan and Piran [10] and Kong et al [11] considered the possibility of tuning the microphysical parameters; Toma et al [4] suggested that summation of many different directed mini-jets may produce shallow decay radiation; Ghisellini et al [12] suggested a late internal shock emission model; Yamazaki 2009 [13] and Liang et al [14] suggested that by shifting the starting time to ∼10 3 s ahead, the shallow decay becomes normal decay automatically. In this Letter we propose an alternative explanation, that the external shock (in a wind environment) [15−18] before the deceleration time produces the shallow decay phase of early x-ray emission.…”
mentioning
confidence: 99%